Jubileuszowe refleksje o Pracowni-Laboratorium Języka i Kultury Ludowej Uniwersytetu Zielonogórskiego = Jubilee reflections on the Laboratory of Folk Language and Culture at the University of Zielona Góra - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the present reflections is to comment on this unique university laboratory - the University Ethnographic Minimuseum, whose resources include artefacts of material and spiritual/ symbolic culture characteristic of Polish folklore. The university laboratory was created, managed and financed - from her own private funds - by Professor Katarzyna Węgorowska.
Keywords: uniwersytecka pracownia; kultura tradycyjna; artefakt; werbalizacja; university laboratory; folk culture; artefact; verbalization